Dynamic versus nondynamic magnetic resonance imaging (MRI) protocols in Ovarian-Adnexal Reporting and Data System for magnetic resonance imaging (O-RADS MRI) scoring of adnexal masses: a comparative performance analysis - PEKER A. A.; DÖNMEZ Z.; AKÇAY A.; TOPRAK H.; Gülteki̇n M. (My University, 2026)
AİM To compare the diagnostic performance of the Ovarian-Adnexal Reporting and Data System for magnetic resonance imaging (O-RADS MRI) using dynamic and nondynamic contrast-enhanced protocols in the characterisation of adnexal masses. MATERİALS AND METHODS This retrospective study included 369 patients (mean age, 43.6 ± 15 years) with 479 adnexal lesions who underwent pelvic MRI between January 2020 and March 2025. Dynamic contrast-enhanced MRI (DCE-MRI) was performed in 97 lesions and nondynamic contrast-enhanced MRI in 382. Two radiologists, with 8 and 4 years of experience, independently reviewed all examinations while blinded to clinical and histopathological data. Lesions scored as O-RADS 2–3 were classified as benign and O-RADS 4–5 as malignant. Histopathology or ≥12 months of imaging follow-up served as the reference standard. Diagnostic accuracy, sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated for both protocols. Results Among 479 lesions, 302 (76.8%) were benign, 28 (7.1%) borderline, and 63 (16.0%) malignant. The dynamic protocol achieved a sensitivity of 97.4%, specificity of 93.2%, PPV of 90.2%, NPV of 98.2%, and accuracy of 94.8%. The nondynamic protocol showed comparable results (sensitivity 96.4%, specificity 94.6%, PPV 91.2%, NPV 97.9%, accuracy 95.0%), with no significant difference in diagnostic accuracy ( P =0.794). Malignancy rates increased progressively with higher O-RADS categories in both protocols. Conclusion O-RADS MRI provides a reliable framework for risk stratification of adnexal masses. Nondynamic contrast-enhanced MRI achieves diagnostic performance equivalent to DCE-MRI and can be confidently used when dynamic acquisition is not feasible, supporting broader clinical adoption of simplified O-RADS MRI protocols.
Keywords: Tıp; Dahili Tıp Bilimleri; Nükleer Tıp; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Nuclear medicine; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Radyoloji Nükleer Tıp ve Medikal Görüntüleme; Clinical Medicine (Med); Clinical Medicine; Radiology Nuclear Medicine & Medical Imaging; Radyoloji, Nükleer Tıp ve Görüntüleme; Radiology, Nuclear Medicine and Imaging